2002
DOI: 10.1063/1.1452221
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastic surface acoustic wave attenuation and anisotropic magnetoresistance in Ni3Fe thin films

Abstract: The vector magnetic field, H, dependencies of 0.6 GHz magnetoelastic Rayleigh-mode surface acoustic wave (SAW) attenuation, A(H), and dc magnetoresistance of polycrystalline Ni3Fe thin films with thicknesses ranging from 5.3 nm to 179.1 nm were measured and correlated with the samples’ uniaxial anisotropy fields, HK. For all samples, low hysteresis, symmetric, resonance-type A(H) response peaks were observed for H⊥HK. The data indicate that a combination of film-substrate stresses and the very small magnetocry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Based on SAW magneto-transmission measurements with the static external magnetic field applied either perpendicular or parallel to the SAW propagation direction, these authors suggested that a magnetoelastic interaction most probably was the dominant interaction mechanism. However, conclusive evidence for the occurrence of an elastically driven, acoustic FMR has proven elusive, and important aspects of the interaction mechanism still await explanation, as stated by Wiegert as recently as 2002 [16].Our experimental study of SAW-based RF spin mechanics as a function of magnetic field magnitude and orientation provides clear evidence for elastically excited, acoustic ferromagnetic resonance. Our findings thus extend the application and understanding of magnetoelastic interaction phenomena in the RF regime.We study the hybrid device depicted schematically in Fig.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Based on SAW magneto-transmission measurements with the static external magnetic field applied either perpendicular or parallel to the SAW propagation direction, these authors suggested that a magnetoelastic interaction most probably was the dominant interaction mechanism. However, conclusive evidence for the occurrence of an elastically driven, acoustic FMR has proven elusive, and important aspects of the interaction mechanism still await explanation, as stated by Wiegert as recently as 2002 [16].Our experimental study of SAW-based RF spin mechanics as a function of magnetic field magnitude and orientation provides clear evidence for elastically excited, acoustic ferromagnetic resonance. Our findings thus extend the application and understanding of magnetoelastic interaction phenomena in the RF regime.We study the hybrid device depicted schematically in Fig.…”
mentioning
confidence: 53%
“…Based on SAW magneto-transmission measurements with the static external magnetic field applied either perpendicular or parallel to the SAW propagation direction, these authors suggested that a magnetoelastic interaction most probably was the dominant interaction mechanism. However, conclusive evidence for the occurrence of an elastically driven, acoustic FMR has proven elusive, and important aspects of the interaction mechanism still await explanation, as stated by Wiegert as recently as 2002 [16].…”
mentioning
confidence: 99%
“…The physics of such heterostructures has been investigated experimentally. [20][21][22][23] Recently, it has been demonstrated that the observed changes of the complex magnetotransmission through a hybrid LiNbO 3 /Ni SAW delay line can be identified with absorption and dispersion signals of a SAW-driven ferromagnetic resonance (FMR). 24 We here use the term FMR synonymously with spin wave resonance (SWR), which is the more appropriate term if the ferromagnet is large compared with the acoustic wavelength and a spin wave mode is excited.…”
Section: Introductionmentioning
confidence: 99%
“…Both kinds of delta-E effect sensors require an external or internal magnetic bias field to be operated at their optimum sensitivities. Besides sensor applications, the delta-E effect has been used for tunable SAW devices operating up to the GHz range [18,19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%